ПРОЦЕССЫ ТРАНСФОРМАЦИИ ЛАНДШАФТОВ ЮЖНОГО ПРИАРАЛЬЯ - Рафиков, В.А.; Рафикова, Н.А.; Ганиев, З.А. (SCIENCE and SOCIETY, 2025)
This article examines the processes of transformation of the Aral Sea region landscapes in the context of intensifying desertification. Particular attention is paid to the diversity of landscape genesis directions, which is determined by a combination of physical and geographical factors. A conceptual model of desertification processes in this region is presented, reflecting the relationship between natural and anthropogenic factors.
Keywords: melioration; desertification; soil salinization; Amu Darya delta; collector-drainage system; water-salt regime; groundwater; land productivity; Aral Sea side